2014
DOI: 10.1063/1.4879680
|View full text |Cite
|
Sign up to set email alerts
|

The effect of structural parameters on the in-plane coupling between quantum dashes of a dense ensemble in the InAs-InP material system

Abstract: In this work, we investigate the importance of lateral electronic coupling in a dense ensemble of anisotropic epitaxial nanostructures called quantum dashes. The respective confined state energy levels and the related tunneling times between two neighboring nanostructures are calculated using a simplified approach with parabolic effective masses in a single band k·p approximation, and assuming infinite size of the quantum dashes in the elongation direction. There has been studied the influence of the cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In general, due to the high planar density of dashes, tunneling effects between the neighboring objects would seem to be feasible. However, we have found that the quantummechanical coupling can be neglected in case of strongly inhomogeneous ensemble of QDashes, 31 which is the case for the self-assembled InAs/InP system considered here.…”
mentioning
confidence: 89%
“…In general, due to the high planar density of dashes, tunneling effects between the neighboring objects would seem to be feasible. However, we have found that the quantummechanical coupling can be neglected in case of strongly inhomogeneous ensemble of QDashes, 31 which is the case for the self-assembled InAs/InP system considered here.…”
mentioning
confidence: 89%
“…4,5) According to the previous reports, 6,7) the electronic state in strongly coupled QDs became delocalized as the interdot spacing is less than about 10 nm. While there have been reports on theoretical studies regarding in-plane strong coupling between adjacent QDs, 8,9) there are fewer experimental studies on self-assembled QDs due to low QD density and large inhomogeneous broadening of the QD size. Recently, we successfully fabricated in-plane ultrahigh density (UHD) QDs of InAs/InAsSb grown epitaxially on GaAs substrates by using MBE.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the abundance of semiconductor nanostructures, those prepared via molecular beam epitaxy (MBE) in InAs on InPsubstrate systems [1], especially InAs/AlGaInAs considered here [2], typically stand out with high areal density and in-plane elongation so high that it is disputable whether they should be classified as quantum dots (QDs) or quantum wires [3][4][5][6]. This fundamental ambiguity did not prevent the intense research on the properties of such objects.…”
mentioning
confidence: 99%